A case of extremity over-exposure and regulatory compliance - Hoyt J Burdick; Tina Shoemaker; Nancy Godby; James Norweck (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2023)
During a routine NRC inspection, a review of historical occupational dosimetry monitoring data for interventional radiology physician AUs was questioned regarding unexpectedly low results. This was interpreted to be an indicator of noncompliance with the wearing of occupational dose monitoring devices and, therefore, required occupation dose reconstructions in order to estimate the actual dose. In an effort to comply with dose monitoring requirements, the AU interventional radiologists diligently began wearing their whole-body and ring dosimeters during all procedures including Y-90, fluoroscopy-guided and CT-guided. In the interest of patient care, an AU that performs many interventional CT-guided procedures involving the use of a cumbersome treatment device, placed his hand in the CT beam on numerous occasions to stabilize the device. This quickly resulted in a cumulative extremity exposure that exceeded allowed limits. Once we became aware of the extremity over-exposure, steps were taken to prevent any further significant extremity exposure for the remainder of the year. The over-exposure was reported to the NRC and State following regulatory requirements.